2018
DOI: 10.1007/s10067-018-4011-8
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate preferentially affects Tc1 and Tc17 subset of CD8 T lymphocytes

Abstract: Rheumatoid arthritis is considered a T-lymphocyte-mediated disease. However, studies have focussed on CD4 T-lymphocytes, ignoring CD8 T-lymphocytes despite the latter being found abundantly in the synovium. Specifically, there is little data of the effect of methotrexate, the gold-standard DMARD, on various CD8 cytokine T-lymphocyte subsets and conflicting data on CD4 subsets. In this prospective study, patients with active rheumatoid arthritis, who were 18 to 65 years of age, were treated with methotrexate (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…We further evaluated the impact of GM on the function of T M cells in terms of cytokine production including IFNγ, TNFα, IL-2, and IL-17. First, we noticed that GM untreated patients and healthy controls had a similar cytokine expression profile, which might reflect a normalization effect exerted by MTX therapy in the GM untreated group (MTX use 74.28%, Table 1); In fact, previous studies have shown a decline in CD8 + IFNγ + cells (24) and a reduction in circulating Th17 subsets after MTX treatment (25). Moreover, long-term therapy with MTX in combination with low dose corticosteroids for RA influenced the predominance of type 1 cytokines toward normalization of the cytokine balance in both CD4 + and CD8 + T lymphocytes (26).…”
Section: Discussionmentioning
confidence: 73%
“…We further evaluated the impact of GM on the function of T M cells in terms of cytokine production including IFNγ, TNFα, IL-2, and IL-17. First, we noticed that GM untreated patients and healthy controls had a similar cytokine expression profile, which might reflect a normalization effect exerted by MTX therapy in the GM untreated group (MTX use 74.28%, Table 1); In fact, previous studies have shown a decline in CD8 + IFNγ + cells (24) and a reduction in circulating Th17 subsets after MTX treatment (25). Moreover, long-term therapy with MTX in combination with low dose corticosteroids for RA influenced the predominance of type 1 cytokines toward normalization of the cytokine balance in both CD4 + and CD8 + T lymphocytes (26).…”
Section: Discussionmentioning
confidence: 73%
“…These characteristics may also account, at least in part, for the extremely favorable clinical behavior of CD8+ cytotoxic T-cell lymphoma type after methotrexate cessation. Very recently, Snadhu et al [31]. reported that methotrexate preferentially affects subsets of CD8+ T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…83 Dividing cytokine production into CD4 + IFN-c + (T h 1), CD4 + IL4 + (T h 2) and CD4 + IL17 + (T h 17) cells, and CD8 + IFN-c + (T c 1), CD8 + IL4 + (T c 2) and CD8 + IL17 + (T c 17) cells, MTX (up to 25 mg/week) significantly decreased the T c 1 subset and increased the T c 17 subset after 24 weeks of treatment in rheumatoid arthritis. 84 Frequencies were not altered in other subsets. Folic acid status also affects cellmediated immunity by reducing circulating T cells.…”
Section: Fae-induced Lymphopenia Linked To Infection and Influencing mentioning
confidence: 83%
“…While MTX induces apoptosis of in vitro activated T cells, it only slightly increased the risk of leukopenia in randomized controlled trials (RCTs) . Dividing cytokine production into CD4 + IFN‐γ + (T h 1), CD4 + IL4 + (T h 2) and CD4 + IL17 + (T h 17) cells, and CD8 + IFN‐γ + (T c 1), CD8 + IL4 + (T c 2) and CD8 + IL17 + (T c 17) cells, MTX (up to 25 mg/week) significantly decreased the T c 1 subset and increased the T c 17 subset after 24 weeks of treatment in rheumatoid arthritis . Frequencies were not altered in other subsets.…”
Section: Discussionmentioning
confidence: 99%